Proximidades Vividas e Recusadas: Subjetividades Femininas em Perto do Coração Selvagem - Araújo, Ana Lúcia Moreira Rios Coimbra de (2010)
This essay has the purpose to understand the structure of subjectivities on the novel Perto do Coração Selvagem from Clarice Lispector, pursueing to keep up the social and historical conditions of this narrative, including those that allowed to insert the writer in a literary field predominantly masculine, To make it possible, was observed the way why the subjectivities emerge as a contrastant mirrors game between narrator and female characters before the wedding, the family, the sexuality, main elements at this process.